Activity-Based Probes for the High Temperature Requirement A Serine Proteases - Nam, Ho Yeon; Song, Dasom; Eo, Jinny; Choi, Na-Eun; Hong, Jong-Ah; Hong, Kyung Tae; Lee, Jun-Seok; Seo, Jiwon; Lee, Jiyoun (AMER CHEMICAL SOC, 2020)
The high temperature requirement A (HTRA) family of serine proteases mediates protein quality control. These proteins process misfolded proteins in several diseases including Alzheimers disease (AD) and Parkinsons disease (PD). While their structures and activation mechanisms have been studied, the precise details of the regulation of their activity under physiological conditions have not been completely elucidated, partly due to the lack of suitable chemical probes. In the present study, we developed novel activity-based probes (ABPs) targeting the HTRAs and demonstrated their utility in the monitoring and quantification of changes in enzyme activity in live cells. Using our probes, we found the activity of HTRA1 to be highly elevated in an AD-like cell-based model. We also observed the active HTRA2 in live cells by using a mitochondrion-targeted probe. We believe that our probes can serve as a useful tool to study the role of human HTRAs in neurodegenerative diseases.
Keywords: FUNCTIONAL-ANALYSIS; HTRA PROTEASES; PDZ DOMAINS; PROTEIN; SPECIFICITY; SELECTIVITY; MECHANISMS; ROLES; DEGP